Zenkov Hypothesis on Pair $р$-Sylow Intersections of Chevalley Groups of Characteristic $р$ - Voitenko, T. Yu.; Levchuk, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We present all Chevalley groups over a finite field of arbitrary characteristic p in which the index of the normalizer of any pair of Sylow p-subgroups is relatively prime with p.